Injury Detector as a Visual Learning Media in Forensic Medicine - Trissanto, Stefanus; Wiraagni, Idha Arfianti; Widagdo, Hendro; Pidada, Ida Bagus Gede Surya Putra (Fakultas Kedokteran Universitas Alkhairaat, 2024)
ABSTRAK Media pembelajaran visual dapat membantu mahasiswa pendidikan profesi kedokteran belajar lebih baik. Injury Detectordapat mendeteksi jenis cedera benda tumpul dalam kedokteran forensik. Injury Detector menyediakan kesempatan dalam pembelajaran interpretasi luka bagi mahasiswa program pendidikan profesi dalam bidang kedokteran forensik. Mengetahui perbedaan proporsi dari hasil belajar antara mahasiswa profesi yang mempelajari interpretasi luka dengan Injury Detectors dan buku teks (E-book) Knight’s Forensic Pathology Fourth Edition. Menggunakan metode deskripsi analitis dengan desain penelitian Cross Sectional, yang dilakukan terhadap 70 mahasiswa pendidikan profesi yang dibagi menjadi 2 kelompok. Kelompok 1 (Pembelajaran Interpretasi Luka Robek dan Memar dengan buku teks (E-Book) Knight’s Forensic Pathology Fourth Edition). Proporsi kedua kelompok dengan Chi-Square, diuji berdasarkan skor dari pre-test, post-test, dan nilai rata-rata dari pre-test dan post-test. Ditemukan perbedaan dalam proporsi dari hasil tes dengan p = .437 (p.0,05) pada pre-test, p = .089 (p > .05) di post-test dan p = .092 (p > .05) pada nilai rata rata pre-test – post-test scores. Injury Detector sebagai media pembelajaran visual yang didukung Artificial Intelligence memperoleh hasil yang baik, sehingga diperlukan komitmen yang kolektif dari lembaga pendidikan, terutama dalam bidang kedokteran forensik, agar dapat mengadopsi kegiatan ini secara efektif. ABSTRACT Visual learning media can help students of medical professional education to learn better. Injury detector as an object detector and able to interpret the type of blunt force injury in Forensic Medicine. Injury Detector provides the latest opportunities in learning wound interpretation for medical professional education program students in the field of Forensic Medicine. Knowing the difference in the proportion of learning outcomes between the medical professional education program students who learn wound interpretation with Injury Detectors and textbooks (E-book) Knight’s Forensic Pathology Fourth Edition. Using analytical description method with analytical cross sectional research design. Conducted on 70 medical professional education program students who were divided into 2 groups, namely Group 1 (Learning Interpretation of Lacerations and Bruises with Textbook (E-book) Knight’s Forensic Pathology Fourth Edition). The proportion of both groups with Chi-Square was tested based on pre-test, post-test, and average pre-test – post-test scores. There is a difference in the proportion of learning outcome test with p = .437 (p>.05) in the pre-test, p = .089 (p > .05) in the post-test and p = .092 (p > .05) in the average pre-test – post-test scores. Injury Detector as a visual learning method supported by Artificial Intelligence obtained good results so that collective commitment from educational institutions, especially in the field of forensic medicine, is needed to adopt this technology effectively.